Adverse childhood experiences and grandiose narcissism – Findings from a population-representative sample. (May 2022) - Clemens, Vera; Fegert, Jörg M.; Allroggen, Marc
Abstract: Background: In the development of narcissism, besides genetic factors, hostile educational conditions, including adverse childhood experiences (ACEs), are discussed as causal factors. ACE may play a causal role in the development of antagonistic behavior due to negative interpersonal experiences. However, studies assessing the role of ACEs in the etiology of narcissism are still inconsistent, particularly regarding grandiose narcissism. This may be due to the complexity of grandiose narcissism, which can be distinguished into agentic (admiration) and antagonistic (rivalry) facets. Understanding the role of early traumatic events in the etiology of grandiose narcissism may be important for psychotherapeutic treatment in both, patients with trauma history and narcissistic patients. Objective: We aimed to specify the role of ACEs in grandiose narcissism by differentiating between admiration and rivalry. Participants and setting: In a cross-sectional survey conducted from November 2017 to February 2018, a representative sample of the German population above the age of 14 ( N = 2531) was selected in a random route approach. Results: Increased numbers of ACEs were associated with higher mean scores for rivalry in females (B = 0.04, p = 0.02) and males (B = 0.08, p < 0.01), while no significant associations were seen for admiration. Focusing on individual ACEs, in males, all maltreatment experiences were associated with narcissistic rivalry, with the exception of physical neglect, while in women only emotional maltreatment and emotional neglect were significant. Associations with household dysfunction were shown only in men. There were no significant associations between individual ACEs and admiration. Conclusions: Our results suggest emotional coldness and negative relationship experiences play a role in the development of, in particular, antagonistic and unfavorable narcissistic traits, such as admiration. Therapy with individuals who have experienced ACEs should take into account possible narcissistic personality traits related to ACEs to facilitate successful treatment. Thus, our findings may help building a therapeutic alliance though a better understanding of the development of current behavioral problems for both patient and psychotherapist. Highlights: Adverse childhood experiences (ACEs) are associated with antagonistic narcissism. ACEs are not associated with agentic narcissism (admiration). This may explain ambiguous results to date regarding ACEs and grandiose narcissism. The relationship between ACEs and grandiose narcissism is more pronounced in males. Child maltreatment is more related to rivalry than household dysfunction.